Novel tryptophyllin peptides from Physalaemus centralis inhibit oxidative stress-induced endothelial dysfunction in rat aorta preparation - Nogueira, Ariane; Brango-Vanegas, José; Vasconcelos, Andreanne G; Coleone, Alex P [UNESP]; Barbosa, Éder A; Moreira, Daniel C; da Silva, Maria da Gloria; Cabral, Wanessa F; Nascimento, Jhones D; Vinícius de Sousa França, José; Arcanjo, Daniel Dias Rufino; Lima, Filipe Camargo D A; et al. (Elsevier, 2025)
Amphibian skin is a rich source of molecules with biotechnological potential, including the tryptophyllin family of peptides. Here, we report the identification and characterization of two tryptophyllin peptides, FPPEWISR and FPWLLS-NH2, from the skin of the Central Dwarf Frog, Physalaemus centralis. These peptides were identified through cDNA cloning and sequence comparison. FPWLLS-NH2 shares its primary structure with a previously identified peptide from the skin of Pelophylax perezi, named PpT-2. Another peptide, FPPEWISR, is novel and was named PcT-1. After solid-phase peptide synthesis, both peptides exhibited significant antioxidant activity, with PcT-1 and PpT-2 demonstrating ABTS radical scavenging capacities of 0.305 and 0.269 mg Trolox equivalents/mg peptide, respectively, and ORAC values of 0.319 and 0.248 mg Trolox equivalents/mg peptide. Additionally, PcT-1 and PpT-2 inhibited AAPH-induced hemolysis in human red blood cells, achieving a protection level comparable to Trolox at 0.2 mg/mL. In rat aorta preparations, both peptides partially restored acetylcholine-induced vasorelaxation following pyrogallol-induced oxidative stress, with a greater protective effect of PpT-2. Hemolytic activity assay indicated no cytotoxicity in human red blood cells, and tests on Galleria mellonella larvae confirmed their low toxicity in vivo. These findings highlight the biotechnological potential of PcT-1 and PpT-2 as antioxidant agents, paving the way for new therapeutic applications in combating oxidative stress-related diseases.